Nano-Sized Cyclodextrin-Based Molecularly Imprinted Polymer Adsorbents for Perfluorinated Compounds—A Mini-Review - Abdalla H. Karoyo (Nanomaterials, 2015)
Recent efforts have been directed towards the design of efficient and contaminant selective remediation technology for the removal of perfluorinated compounds (PFCs) from soils, sediments, and aquatic environments. While there is a general consensus on adsorption-based processes as the most suitable methodology for the removal of PFCs from aquatic environments, challenges exist regarding the optimal materials design of sorbents for selective uptake of PFCs. This article reviews the sorptive uptake of PFCs using cyclodextrin (CD)-based polymer adsorbents with nano- to micron-sized structural attributes. The relationship between synthesis of adsorbent materials and their structure relate to the overall sorption properties. Hence, the adsorptive uptake properties of CD-based molecularly imprinted polymers (CD-MIPs) are reviewed and compared with conventional MIPs. Further comparison is made with non-imprinted polymers (NIPs) that are based on cross-linking of pre-polymer units such as chitosan with epichlorohydrin in the absence of a molecular template. In general, MIPs offer the advantage of selectivity, chemical tunability, high stability and mechanical strength, ease of regeneration, and overall lower cost compared to NIPs. In particular, CD-MIPs offer the added advantage of possessing multiple binding sites with unique physicochemical properties such as tunable surface properties and morphology that may vary considerably. This mini-review provides a rationale for the design of unique polymer adsorbent materials that employ an intrinsic porogen via incorporation of a macrocyclic compound in the polymer framework to afford adsorbent materials with tunable physicochemical properties and unique nanostructure properties.